The Excess Power Puzzle of the EU Budget - Heikki Kauppi; Mika Widgrén (Aboa Centre for Economics (ACE), 2009)
It is a constant topic of debate how the European Union (EU) spends the money it collects from its member states. This paper supports the idea that the EU budget battle involves one-shot games that have persistent impacts on the budget allocations. In one way or the other, the member states are able to establish rules or contracts that restrict the budget allocation in advance. In the current status quo, France and Spain are the clearest winners of these restrictions, while Austria, Finland and Sweden, not to mention the new member states, suffer largest losses.
Keywords: C71; D70; D72; 330; EU budget; voting power